DIVERSITY OF WATER ENVIRONMENT GASTROPODA IN A EMPAYANG-KASAP RIVER IN THE DISTRICT LAHAT - Hecca, Desven; Hidayat, Saleh; Dewiyeti, Susi (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2017)
This research has been conducted with the tittle the diversity of gastropods on the river water environment Empayang Lahat regency of South Sumatra province. The aim of this research species diversity of gastropods contained the region. This research was implemented conducted in October 2015, a river Empayang Kasap Sukajadi Lahat regency. The methods of this research is purposive random sampling method with 5 sampling stations, each station is divided into three substations (edges first, middle, edge 2) was determined by linear transects (line transect). The data of the sample was taken in the morning and afternoon. The results of this research were obtained 8 species of gastropods (Melanoides granifera, Elimia acuta, Brotia tetidinaria, Lymnae stagnalist, Lymnae rubiginosa, Pomacea canaliculata, Pila polita and Menetus sp) with 7 genus, and of the six tribes (families) of 4 order. The total index of the diversity in the river Empayang Kasap Sukajadi Lahat district was of 2.09 to 2.46. The highest levels of diversity found in the station V (2.46) and the lowest at station I (2.09). While the value of dominance index (C) with a range of 0.17 to 0.26 at five stations in the lower state, the highest level of dominance index at station I (0.26) and the lowest at station III (0.17). River water quality conditions greatly affect the existence of gastropods.